Burden of Salmonella Typhi Isolated from Bloodstream Infection from 2015 to 2020: A Systematic Review and Meta-analysis - Zeba, Zebunnesa; Hasan, Shariar Talukder; Sumit, Ahmed Faisal; Yusuf, Md Abdullah (Bangladesh Journal of Infectious Diseases, 2023)
Background: Bangladesh is a major contributor to the global problem of typhoid fever, which is predominantly caused by Salmonella typhi. This is due to Bangladesh’s subpar healthcare standards, inadequate cleanliness standards, and inappropriate and excessive use of antibiotics. Objective: Salmonella typhi antibiotic resistance and the current situation of typhoid fever in Bangladesh were the subjects of this systematic review. Methodology: Finding publications about Salmonella typhi in Bangladesh published between 2015 and 2020 required searching Google Scholar, PubMed, and Bangladesh Journals Online with pertinent keywords. A predetermined set of criteria determined who would be included or excluded. Results: Initially,50 articles were retrieved. Using PRISMA flow chart 5 were selected for the study. Through forest plot, the overall effect size is found 0.28 which is represented by a diamond with confidence interval of 0.06 – 0.50. Since the confidence interval does not cross the threshold of no impact, the p value is 0.00. We can conclude that the overall effect is statistically significant. Microsoft excel was used to figure out the trend of antibiotic resistance. The effect size of an article was 0.08 (95%CI 0.05 – 0.11) and weighted 20.44%. Another study was reported with the effect size of 0.07 (95%CI 0.00 – 0.14) and weighted 20.07%. Conclusions: S. typhi was shown to be quite prevalent, and there were also significant surveillance and data gaps in the research’ methodological data. Bangladesh Journal of Infectious Diseases, June 2023;10(1):3-10